AHP-GeoTOPSIS method to analyze priority areas for sugarcane plantation development in Lamongan Regency. Issue 1 (January 2022) - Artikanur, S D; Widiatmaka,; Setiawan, Y; Marimin,
Abstract: Sugar imports are carried out every year in Indonesia to meet domestic needs. The average sugar imports from 2015 to 2019 reached 4.34 million tons. The Spatial Plan of Lamongan Regency 2011-2031 proclaims the development of sugarcane plantations, but the priority assessment of the development area which takes into account the balance of sugarcane availability in the future has not been scientifically studied. This study aimed to analyze the priority areas for sugarcane plantation development in Lamongan Regency. Analysis of development priorities was carried out using the AHP-GeoTOPSIS method and involving six experts. The criteria used include the number of agricultural households, suitability, and availability of land for sugarcane, population, and the balance of sugarcane availability in each sub-district. Land use datasets were used to calculate the suitability and availability of land and the balance of sugarcane availability in each sub-district. Based on the analysis, there were five priority areas for land development. There four subdistricts to be developed are as follows: Ngimbang, Solokuro, Mantup, and Kedungpring with weight values of 0.797, 0.776, 0.726, and 0.683, respectively. The study results can be used as input for the development of sugarcane plantations within the spatial plan of Lamongan Regency.